Peran Analis Hukum Dalam Penyusunan Kebijakan Pada Kantor Wilayah Kementerian Hukum Dan Hak Asasi Manusia - Hutagalung, Jordy William; Simamora, Janpatar (Bacarita Law Journal, 2025)
The formulation of effective and equitable public policies is one of the important aspects in ensuring the achievement of good governance objectives. In this context, the role of legal analysts in the Regional Office of the Ministry of Law and Human Rights (Kanwil Kemenkumham) has great significance. Legal analysts are responsible for ensuring that policies are not only in accordance with applicable legal norms, but are also fair, provide legal certainty, and respect human rights. Their main tasks include reviewing existing laws and regulations, identifying the potential legal impacts of proposed policies, and providing recommendations for policy improvements where necessary. In addition, legal analysts also play an important role in analyzing the possibility of legal uncertainty or regulatory conflicts that could harm society. Nevertheless, legal analysts are faced with various challenges, such as the complexity of overlapping regulations, rapid changes in social and political dynamics, and the need to accommodate different interests. Therefore, to improve policy effectiveness, capacity building and collaboration between various parties involved in policy-making are required, as well as continuous evaluation of policy implementation. Thus, the success of public policy is highly dependent on the ability of legal analysts to maintain a balance between compliance with the law and the fulfillment of community needs in a fair and responsive manner.